Online sexual activities in Hispanic women: A chance for non-heterosexual women - Giménez-García, Cristina; Ruiz-Palomino, Estefanía; Gil-Llario, María Dolores; Ballester-Arnal, Rafael (Revista de Psicopatología y Psicología Clínica, 2020)
Abstract: Sexuality is still modulated by social determinants that promote a passive role for women. In the recent decades, some findings have supported the influence of the Internet on sexuality. However, the relevance of online sexual activities for some groups such as Hispanic young women is still unknown. In this context, this study examines online sexual experience among 310 Hispanic women from Argentina, Mexico and Spain; as well as the role of their offline sexuality and country in this sexual pattern. As a result, Hispanic women report a variety of online sexual activities that ranges from searching information to masturbation. In particular, the Internet use for sexual purposes is more common for homosexual and bisexual women. Therefore, the Internet may be a new context to explore sexuality for Hispanic women, particularly for those who self-identified as lesbians and bisexuals. Keywords: Online sexual activities; Hispanic culture; young people; women; sexual orientation. Actividades sexuales online en mujeres hispanas: ¿una oportunidad para mujeres no heterosexuales? Resumen: La sexualidad todavía está modulada por determinantes sociales que favorecen un rol pasivo entre las mujeres. Desde hace algunas décadas, algunos hallazgos han apoyado la influencia de internet en la sexualidad. Sin embargo, la importancia de las actividades sexuales online para algunos grupos como las mujeres jóvenes hispanas todavía es desconocida. En este contexto, este estudio examina la experiencia sexual online entre 310 mujeres hispanas de Argentina, México y España, así como el rol de la sexualidad offline y su procedencia en este patrón de conducta. Como resultado, las mujeres hispanas reportan variedad de conductas sexuales online que abarcan desde la búsqueda de información hasta la masturbación. En particular, el uso de internet con propósitos sexuales es más común entre las mujeres homosexuales y bisexuales. Así pues, internet podría suponer un nuevo contexto para explorar la sexualidad entre las mujeres hispanas, en particular, para aquellas que se identifican con la homosexualidad y la bisexualidad. Palabras clave: Actividades sexuales online; cultura hispana; juventud; mujeres; orientación sexual.